Gravity Sensing, Graviorientation and Microgravity - Häder, Donat-Peter; Braun, Markus; Hemmersbach, Ruth (Gravitational Biology I - Gravity Sensing and Graviorientation in Microorganisms and Plants, 2018)
Gravity has constantly governed the evolution of life on Earth over the last 3.5 billion years while the magnetic field of the Earth has fluctuated over the eons, temperatures constantly change, and the light intensity undergoes seasonal and daily cycles. All forms of life are permanently exposed to gravity and it can be assumed that almost all organisms have developed sensors and respond in one way or the other to the unidirectional acceleration force. Here we summarize what is currently known about gravity sensing and response mechanisms in microorganisms, lower and higher plants starting from the historical eye-opening experiments from the nineteenth century up to today's extremely rapidly advancing cellular, molecular and biotechnological research. In addition to high-tech methods, in particular experimentation in the microgravity environment of parabolic flights and in the low Earth orbit as well as in "microgravity simulators" have considerably improved our knowledge of the fascinating sensing and response mechanisms which enable organisms to explore and exploit the environment on, above and below the surface of the Earth and which was fundamental for evolution of life on Earth.
CRIS-Team WoS Importer:2019-04-18